Catch me if you can: The interplay between the incumbent and the regulator in the Italian telecommunications market - Enzo Pontarollo; Paolo Gerli (International Telecommunications Society (ITS), 2014)
In Italy, fixed telecommunications were liberalised 15 years ago, but the incumbent is still the dominant operator. The Italian antitrust authority has recently fined Telecom Italia for margin squeeze and technical sabotage, proving that the incumbent still has the incentive and the power to deploy anticompetitive conducts. This research studies Telecom Italia's anticompetitive behaviours and regulatory interventions from 2004 to 2012, in order to understand and assess how the incumbent's strategies are affected by regulation. Four wholesale markets (local loop unbundling, colocation, wholesale broadband access, wholesale line rental) and two retail markets (directories and non-geographic numbers) have been considered. For each market, both Telecom Italia's strategies and NRA's actions have been analysed and tracked in a timeline to show the interplay between the incumbent and the regulator and to assess the regulation effectiveness in preventing and discouraging anticompetitive conducts.
Keywords: 330; Anticompetitive conducts; market foreclosure; vertical integration; ex-ante regulation; ex-post regulation; price discrimination; non-price discrimination